Accounting standards for central banks - Courtis, Neil; Mander, Benedict (London : Central Banking Publications Ltd, 2003)
Accounting Standards for Central Banks aims to offer readers an insight into Key debates and emerging best practice in central bank financial reporting.
Includes bibliographical references.
rpm 10/09/13
Loans
Keywords: Banks and banking -- Accounting; Banks and banking, Central; Accounting -- Standards; Disclosure in accounting; Financial instruments -- Accounting